Imperatorin Ameliorates the Aging-Associated Porcine Oocyte Meiotic Spindle Defects by Reducing Oxidative Stress and Protecting Mitochondrial Function - Luo, Dan; Zhang, Jia-bao; Li, Sheng-peng; Liu, Wen; Yao, Xue-rui; Guo, Hao; Jin, Zhe-long; Jin, Yong-xun; Yuan, Bao; Jiang, Hao; Kim, Nam-Hyung (Frontiers in Cell and Developmental Biology, 2020)
Imperatorin (IMP) exhibits a variety of pharmacological properties, including antioxidant, anti-inflammatory, antibacterial, anti-cancer, and anti-hypertension activities. However, its effects on animal reproduction systems, especially oocyte development, maturation, and aging are not yet clear. In this study, the effects of IMP on oocyte development and aging as well as the underlying molecular mechanisms were explored. Oocytes were cultured for an additional 24 h for aging. Results revealed that the blastocyst formation and hatching rates of embryos, which were parthenogenetically activated aged oocytes, were significantly increased with IMP treatment (40 μM). Simultaneously, well-distributed cortical granules but no significant difference in zona pellucida hardness were observed after IMP treatment. During this stage, intracellular reactive oxygen species, apoptosis, and autophagy levels were decreased, while mitochondrial membrane potential, glutathione level, and activity of superoxide dismutase and catalase were increased. IMP-treated aged oocytes also showed significantly higher expression of MOS, CCNB1, BMP15, and GDF9 than non-IMP-treated aged oocytes although their levels were still lower than those in the fresh oocytes. These results suggest that IMP can effectively ameliorate the quality of aged porcine embryos by reducing oxidative stress and protecting mitochondrial function.